Atypical Suprasellar Neurocytoma in a 31-Month-Old Child: A Case Report - Roels, P.; De Beul, P.; Herregods, N. (Journal of Pediatric Neurology, 2017)
We report a case of a 31-month-old girl with visual impairment. Magnetic resonance imaging showed a large cystic lesion with a mural nodule in the suprasellar region. Biopsy was performed, and histopathological examination demonstrated an atypical extraventricular neurocytoma (EVN). EVN is a rare neuroepithelial tumor with similar histological and biological characteristics in comparison to intraventricular neurocytoma. However, the morphological appearance of EVN can show wide variability with significant overlap of imaging findings compared with other neoplasms. The majority of EVNs are seen supratentorial involving the cerebral hemispheres. An EVN in the sellar or suprasellar region has only been reported twice in adults and to our knowledge never in children.
Keywords: EVN; extraventricular; neurocytoma; sellar; suprasellar; child; MRI